ESTIMATION OF THE STOCK OF INDIAN SCAD FISH (Decapterus russeli) LANDED AT THE SIBOLGA ARCHIPELAGO FISHERY PORT, NORTH SUMATRA - Nababan, Sri Megawati; Akmal, Akmal; Wiyanto, Eko; Putra, Yudha Erlangga (Asian Journal of Aquatic Sciences, 2023)
Indian Scad Fish (Decapterus russeli) are the most dominant small pelagic fish resources landed in the Sibolga Archipelago Fisheries Port. The production of Indian Scad Fish catches that are landed in PPN Sibolga on average fluctuates every year. Therefore, it is necessary to analyze the catch of Indian Scad Fish to control the level of exploitation and create effective fishing operations so that the utilization of Indian scad fish resources can run optimally and sustainably. This study aims to determine the percentage level of utilization of Indian scad fish (Depterrus russeli) that landed at the Sibolga Nusantara Fisheries Port, North Sumatra. This research was conducted in March – April 2022. The method used in this research is the survey method. The type of data collected is secondary data. The data analysis used includes standardization of Indian scad fish fishing gear, sustainable potential and optimum effort, total allowable catch (TAC), utilization rate, and effort. From the research results, it was found that the highest production of Indian scad fish catches in 2019 was 6,392 tons. Based on the calculation of MSY and the optimum effort in 2017-2021 of 5,934.97 tons/year, meaning that the maximum catch of Indian scad fish that can be caught is 5,934.97 tons/year and the number of allowable catches is 4,747.98 tons/year or 80% of the maximum catch and utilization rate of Indian scad fish for 5 years is 81.41%.